BUDAYA ORGANISASI SEBAGAI PREDIKTOR PARTISIPASI PENGANGGARAN DAN IMPLIKASINYA PADA SENJANGAN ANGGARAN - Prawira, Hangga; Wirasedana, I Wayan Pradnyantha (E-Jurnal Akuntansi; Vol 14 No 1 (2016), 2016)
This study aims to investigate the influence of direct and indirect relationships between organizational culture on budgetary slack with the participation of budgeting as a mediating variable. Research carried out in the entire Department of Tabanan with a total of 16 SKPD and 3 copies of the questionnaire for each SKPD, bringing the total there are 48 copies of the questionnaire were distributed. Samples was determined using purposive sampling techniques, by taking each Head of Department, Head of Sub Division of Finance Department, and the finance department staff who have had a minimum term of one year budgeting period. Testing hypotheses using path analysis techniques. Results of hypothesis testing showed each had a direct effect is positive and significant relationship to the organizational culture of participation budgeting, organizational culture on budgetary slack, budgeting and participation of the budgetary slack. Variables significantly budgeting participation mediate indirect influence between organizational culture and budgetary slack.
Keywords: Organizational Culture, Budgeting Participation, Budgetary Slack